Who Supports the Humanities in Maine? The Benefits (and Challenges) of Volunteerism - Bischof, Libby (Maine Policy Review, 2015)
Many Mainers give generously of their time to hundreds of local organizations that support and promote the humanities in Maine—especially local libraries, museums, historical societies, and friends groups organized around preservation. In this article Libby Bischof draws heavily on interviews with paid and volunteer staff at such institutions to create a picture of the benefits and challenges of volunteerism.
Keywords: humanities; cultural institutions; volunteers; Maine